Evaluation of anthropometric characteristics and physical abilities in a soccer season: comparison between U-15, U-17 and U-19 - Silva, Rui (2017)
The aim of this study was to examine the development of anthropometric characteristics and physical capacities in a sports season, in young soccer players. A total of 50 players, U-15 (n= 16, 14.0±0.1 years), U-17 (n= 14, 15.6±0.5 years) and U-19 (n= 20, 17.2±0.7 years) were monitored in 3 different moments: after the preparation period (pre-season), after the 1st competitive phase (mid-season) and after the 2nd competitive phase (post-season). To the anthropometric analysis, the height, body mass, muscle mass, fat mass and body girths were evaluated. The aerobic resistance, the work developed by the lower limbs during a vertical jump, the power of the lower limbs during a sprint, the agility and the flexibility were evaluated for the physical capacity analysis. Along the season, there was an increase in body mass and a stabilization of the fat mass due to an increase of the muscle mass. In general, regardless the age group, physical abilities improved from pre-season to mid-season, and then stabilized till the post-season. Understanding the variations through a season, according to the competitive environment and their developmental age, may be a useful tool for control and evaluation of the training process.